Brand Equity, Brand Image, Perceived Value and Behavioural Intentions Nexus: A Mediation Model in an Emerging Market - Oppong, Peter Kwasi; Maama, Haruna (International Review of Management and Marketing, 2026)
This paper evaluates how brand image and perceived value intervene in the relationship between brand equity, which is conceptualized as perceived quality and brand credibility, and behavioural intentions in an emerging market. Structured questionnaires were used to gather data from 265 customers through a systematic sampling procedure. The hypotheses were tested using structural equation modelling in Smart PLS 3. The findings show that perceived value partially mediates the interaction between brand equity and behavioural intentions, and fully mediates the link between brand image and behavioural intentions. Similarly, brand image partially mediates the link between brand equity and perceived value. The study, therefore, establishes that perceived value is a critical success factor when building brand equity and brand image to reinforce behavioural intentions. Brand image also plays a crucial role in strengthening the effect of brand equity on perceived value in the emerging herbal market. This research provides a clear strategic blueprint for managers: while building a credible, high-quality brand is essential, it is the customer’s perception of value that ultimately converts brand strength into repeat purchases, premium pricing, and positive word-of-mouth. The study empirically confirms that perceived value is the indispensable lever for turning brand equity into commercial success in the herbal industry.